Physical Education as a means of health and working efficiency improvement of population; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Khasanova R. R. Rezeda Rakhmatullovna; Sarycheva T. V. Tatiana Valerievna; Soboleva A. A. Antonina Aleksandrovna; Andreev V. I. Vladimir Igorevich; Zagrevsky O. I. Oleg; Nikonova D. U. Darya; Smagliy L. V. Liudmila (2016, 2016)
Title screen